(untitled) (London Journal of Research In Humanities and Social Sciences, 2026)
The aim of this project is to improve the quality of life for children with autism in school environments and to promote inclusive education from an early age through play. To inform the design process, the study combined a review of relevant literature with direct engagement with children with autism and their families, through 57 interviews. This approach allowed the identification of key challenges faced by these children, including limited understanding from peers and teachers, communication difficulties, and other social barriers. Based on these insights, Auri was developed-an interactive game in the shape of a lighthouse, designed for preschool classrooms. It integrates a pictogram-based communicator-a form of augmentative and alternative communication (AAC)-with a sensory projector, allowing children to interact with pictograms and play audiovisual content that supports relaxation, entertainment and learning. Compared to existing tools for autistic children, which typically focus on either communication or sensory stimulation, Auri integrates both didactic and sensory experiences into a single interactive system.